The Effect of Analogy, Explicit and Discovery Learning on Performance Breakdown under Psychological Pressure - Zahra Asgari; Behrouz Abdoli (University of Tehran, 2013)
The aim of this study was to compare the performance of analogy (implicit),explicit and discovery learning in the retention and transfer of a topspin shot underpsychological pressure. For this purpose, 36 volunteer high school students wererandomly allocated to three treatment conditions: explicit, analogy, and discoverylearning. After performing 300 trials in the acquisition phase, an immediateretention and transfer test under psychological pressure was performed. Before theacquisition phase, the MSRSQ, after the test, a procedural protocol and CSAI-2Qin two phases were completed by the participants. Results showed no significantdifference among the groups in the immediate retention test. In the transfer test,analogy learning group outperformed the two other groups. In addition, contraryto the analogy group, the two other groups experienced a performance breakdownin the transfer test when compared with the immediate retention test. There was asignificant correlation (positive and negative respectively) between their MSRSQscore and number of verbal rules and their performance under pressure. It appearsthat the dominant process in discovery learning is explicit process. In addition,learning under explicit and implicit conditions for an extended period of timeappears to be quantitatively similar but qualitatively dissimilar; therefore, usinganalogy learning, performers benefit from advantages of resistance againstperformance breakdown under psychological pressure.